A Comparative Study of Lateral Sphincterotomy Vs Topical Application of Glyceryl Trinitrate 0.2% in the Treatment of Chronic Anal Fissure an Observational Study - Raheel Azhar, Aabya Salim, Raazia Ramzan, Areeba Mahmood, Saad Aslam, Sidra Riaz (Pakistan Journal of Medical & Health Sciences, 2023)
0.2% Glyceryl trinitrate is vastly used for treatment of chronic anal fissure and it has proven its effectiveness by decreasing anal tone and promoting healing. However, lateral sphincterotomy is considered a standard treatment for anal fissures. OBJECTIVE: The aim of our study was to compare application of 0.2% GTN and lateral sphincterotomy as a treatment for chronic anal fissure. STUDY DESIGN: It was an observational prospective cohort study. METHODOLOGY: This study was conducted in General Surgery unit 2 of Dow University Hospital Ojha, Karachi. A total of 192 participants were included in the study with their signed consent 96 of whom were given GTN and the remaining 96 were advised lateral sphincterotomy RESULTS: Both treatment modalities showed promising results. Upon follow up after 2 and 4 weeks, patients’ symptoms decreased more in the lateral spincterotomy group. Around 29.17% patients became asymptomatic at 2weeks and 87.5% at 4 weeks in the lateral spincterotomy group. While 11.46% became asymptomatic at 2 weeks and 87.5% at 4 weeks in the conservative management group. CONCLUSION: Lateral sphincterotomy shows more effective results in treating chronic anal fissure as compared to application of 0.2% GTN however, as 0.2% GTN has quite comparable results as well, surgeons should opt for it as the first line of management before resorting to lateral sphincterotomy. Keywords: Chronic anal fissure, 0.2% Glyceryl Trinitrate, lateral sphincterotomy.